Ecourse registration system chatbot / Muhammad Hakimi Md Saad - Md Saad, Muhammad Hakimi (2022)
Based on the title, eCourse Registration System AI Chatbot title, the chatbot will be powered by Artificial Intelligence. During COVID-19, the biggest pandemic ever humanity faced, the intelligent chatbot has skyrocketed due to social distancing restrictions. People are required to stay at home and buy their needs in online shopping stores. The development of natural language processing in artificial intelligence has enhanced the chatbot system, typically used in customer service or frequently asked questions (FAQ). This paper has six (6) chapters, which is each chapter explaining indepth the project. The first chapter contains the problem statement, the objectives, project scope, and significance of this project. The second chapter is the literature review of this project, explaining how the research, the methodology, and the findings have been done to develop the chatbot. Basically, an explanation or illustration of each chapter has its purpose.